Barriers and Enablers to Medication Deprescribing among older patients attending a Geriatric Clinic in Southwestern Nigeria: A Cross-Sectional Study. (2023)
Introduction: Polypharmacy is an increasing health problem, leading to rise in morbidity and mortality, especially among older patients. Deprescribing has been recommended for managing polypharmacy, but deprescribing medication in older patients is still uncommon (1). Safe deprescribing interventions can reduce exposure to inappropriate polypharmacy among older patients. However, few empirical data exist on the barriers and enablers to medication deprescribing among older patients in sub-Saharan African countries. Aim: This study aimed to assess the barriers and enablers of medication deprescribing among older patients. Methods: A cross-sectional study of 415 older patients aged ≥60 years, selected consecutively at the geriatric clinic in a Tertiary Hospital was carried out between May and July 2022. An interviewer-administered semi-structured questionnaire was used to obtain information on their sociodemographic characteristics, and barriers and enablers.